Antioxidant Activity of Lawsonia inermis Extracts Inhibits Chromium(VI)-Induced Cellular and DNA Toxicity. (20th June 2011) - Guha, Gunjan; Rajkumar, V.; Kumar, R. Ashok; Mathew, Lazar
Abstract : Hexavalent chromium Cr(VI) is a very strong oxidant which consequently causes high cytotoxicity through oxidative stress. Prevention of Cr(VI)-induced cellular damage has been sought in this study in aqueous and methanolic extracts of Lawsonia inermis Linn. (Lythraceae), commonly known as Henna . The extracts showed significant ( P < .05) potential in scavenging free radicals (DPPH and ABTS + ) and Fe 3+, and in inhibiting lipid peroxidation. DNA damage caused by exposure of pBR322 to Cr(VI)-UV is markedly inhibited by both extracts in varying degrees. A distinct decline in Cr(VI)-induced cytotoxicity was noticed in MDA-MB-435S (human breast carcinoma) cells with an increase in dosage of both extracts individually. Furthermore, both extracts proved to contain a high content of phenolic compounds which were found to have a strong and significant ( P < .05) positive correlation to the radical scavenging potential, lipid peroxidation inhibition capacity and cyto-protective efficiency against Cr(VI)-induced oxidative cellular damage. HPLC analysis identified some of the major phenolic compounds in both extracts, which might be responsible for the antioxidant potential and the properties of DNA and cyto-protection. This study contributes to the search for natural resources that might yield potent therapeutic drugs against Cr(VI)-induced oxidative cell damage.